Pengembangan Media Pembelajaran Matematika Berbasis Android Menggunakan Articulate Storyline 3 pada Materi Integral Fungsi Aljabar Kelas XI SMA Negeri 3 Kupang - Yance, Meliani; Ekowati, Ch. Krisnandari; A. Halim, Fransiska (FKIP Universitas Mataram, 2025)
This study aims to develop a mathematical learning media based on Android using articulate storyline 3 on the material integral algebra class XI SMA Negeri 3 Kupang valid, practical, and effective named ITTFA (Integral indeterminate algebraic functions). The research method used is research development using ADDIE development model which consists of 5 stages, namely Analysis (analysis), Design (design), Development (development), Implementation (implementation), and evaluation (evaluation). Data collection was obtained through interviews, questionnaires, and tests. The results showed that the developed media has met the eligibility criteria of the media, which is valid, practical, and effective. RTV media by 3 media experts and material of 4.50 with the category “valid”. RTP media by teachers is 4.83 with the category of “practical”, RTP media by students on a small scale is 4.67 and students on a large scale is 4.36 with the category of “practical”. The percentage of completeness of post test results of students in small-scale trials was 80% with the category “effective” and large-scale trials were 77% with the category “effective”. Thus, ittfa media is suitable for use in the learning process at school.